Ecophysiological Performance of Proteaceae Species From Southern South America Growing on Substrates Derived From Young Volcanic Materials - Delgado, M.; Zúñiga-Feest, A.; Reyes-Díaz, M.; Barra, P. J.; Ruiz, S.; Bertin-Benavides, A.; Valle, S.; Pereira, M.; Lambers, H. (Frontiers in Plant Science, 2021)
Southern South American Proteaceae thrive on young volcanic substrates, which are extremely low in plant-available phosphorus (P). Most Proteaceae exhibit a nutrient-acquisition strategy based on the release of carboxylates from specialized roots, named cluster roots (CR). Some Proteaceae colonize young volcanic substrates which has been related to CR functioning. However, physiological functioning of other Proteaceae on recent volcanic substrates is unknown. We conducted an experiment with seedlings of five Proteaceae (Gevuina avellana, Embothrium coccineum, Lomatia hirsuta, L. ferruginea, and L. dentata) grown in three volcanic materials. Two of them are substrates with very low nutrient concentrations, collected from the most recent deposits of the volcanoes Choshuenco and Calbuco (Chile). The other volcanic material corresponds to a developed soil that exhibits a high nutrient availability. We assessed morphological responses (i.e., height, biomass, and CR formation), seed and leaf macronutrient and micronutrient concentrations and carboxylates exuded by roots. The results show that G. avellana was less affected by nutrient availability of the volcanic substrate, probably because it had a greater nutrient content in its seeds and produced large CR exuding carboxylates that supported their initial growth. Embothrium coccineum exhibited greater total plant height and leaf P concentration than Lomatia species. In general, in all species leaf macronutrient concentrations were reduced on nutrient-poor volcanic substrates, while leaf micronutrient concentrations were highly variable depending on species and volcanic material. We conclude that Proteaceae from temperate rainforests differ in their capacity to grow and acquire nutrients from young and nutrient-poor volcanic substrates. The greater seed nutrient content, low nutrient requirements (only for G. avellana) and ability to mobilize nutrients help explain why G. avellana and E. coccineum are better colonizers of recent volcanic substrates than Lomatia species.